Relationships between levels of motor coordination, attention and physical activity in children: The mediation model - Jakub Kokštejn; Rudolf Psotta; Pavel Frýbort (Palacky University, 2012)
BACKGROUND: Current findings suggest that physical activity of children with developmental difficulties may be limited by low level of motor coordination. Motor difficulties are often connected with children suffering from attention deficit disorder. OBJECTIVE: The aim of the study was to find out the level of physical activity (PA) in older school-age children with motor difficulties (MD) in comparison with children without MD and to reveal possible mediate impact on attention between the level of motor skills and PA in children of this age. METHODS: Participants were divided into two groups: 15 children with MD (age 13.7 ± 1.6 years) and 27 children without MD (age 13.3 ± 1.4 years). Motor functions were assessed by means of test battery MABC-2, weekly physical activity by means of Actigraph accelerometer and attention by both d2 and numeric square tests. To estimate the mediation of the attention level we have used Baron's & Kenny's (1986) analysis. RESULTS: In most of the indicators of PA, children with MD reached lower value than those without MD. The differences of statistical significance were found in the number of steps per week and weekdays (d = 0.50 and 0.64 respectively) and in PA of a very high intensity (d =2 .00) in boys with and without MD. In girls with MD we have found out significantly less time spent in vigorous intensity PA (d = 0.86). The study results support the hypothesis of developmental motor deficits to be a risk factor for PA in older school-age children. Significant mediation effect of concentration of attention in the relationship between the level of motor skills and PA was observed in three cases - in the relationship between gross motor skills on the one hand, and energy expenditure per week and weekdays, and vigorous intensity PA per week on the other. The amount of mediation effect of attention concentration ranged between 12-22%. CONCLUSION: The study has indicated that children's participation in PA can be strongly influenced by the level of their interceptive and targeting skills, in which visuomotor coordination lies, and that reduced the child's ability to concentrate may be one of the mediate factors causing lower PA.